Astragaloside IV Alleviates the Experimental DSS-Induced Colitis by Remodeling Macrophage Polarization Through STAT Signaling - Tian, Lianlian; Zhao, Jun-Long; Kang, Jian-Qin; Guo, Shi-bo; Zhang, Nini; Shang, Lei; Zhang, Ya-Long; Zhang, Jian; Jiang, Xun; Lin, Yan (Frontiers in Immunology, 2021)
Inflammatory bowel disease (IBD) is characterized by chronic and relapsing intestinal inflammation, which currently lacks safe and effective medicine. Some previous studies indicated that Astragaloside IV (AS-IV), a natural saponin extracted from the traditional Chinese medicine herb Ligusticum chuanxiong, alleviates the experimental colitis symptoms in vitro and in vivo. However, the mechanism of AS-IV on IBD remains unclear. Accumulating evidence suggests that M2-polarized intestinal macrophages play a pivotal role in IBD progression. Here, we found that AS-IV attenuated clinical activity of DSS-induced colitis that mimics human IBD and resulted in the phenotypic transition of macrophages from immature pro-inflammatory macrophages to mature pro-resolving macrophages. In vitro, the phenotype changes of macrophages were observed by qRT-PCR after bone marrow-derived macrophages (BMDMs) were induced to M1/M2 and incubated with AS-IV, respectively. In addition, AS-IV was effective in inhibiting pro-inflammatory macrophages and promoting the pro-resolving macrophages to ameliorate experimental colitis via the regulation of the STAT signaling pathway. Hence, we propose that AS-IV can ameliorate experimental colitis partially by modulating macrophage phenotype by remodeling the STAT signaling, which seems to have an essential function in the ability of AS-IV to alleviate the pathological progress of IBD.